Pathological Complete Response of Duodenal Cancer Following Neoadjuvant S-1/CDDP Chemotherapy: A Case Report - Komine, Kazumasa; Sasaki, Akitaka; Eto, Ken; Iwase, Ryota; Ogawa, Masaichi; Nakaseko, Yuichi; Usuba, Teruyuki (The Japanese Journal of Gastroenterological Surgery, 2025)
A 66-year-old male presented to a local clinic with chief complaints of melena and palpitations. Upper gastrointestinal endoscopy revealed a type 2 lesion in the duodenum, and he was referred to our department with a diagnosis of duodenal cancer. CT imaging indicated that the 12p lymph nodes were compressing the inferior vena cava and the portal vein, initially suggesting that curative resection was not feasible. To address the obstruction, gastrojejunostomy was performed. The patient then underwent three courses of chemotherapy with S-1 and CDDP, resulting in substantial shrinkage of the primary tumor and the involved lymph nodes. Four months after bypass surgery, pancreatoduodenectomy was performed with curative intent. Pathological examination of the resected specimen, including the 12p lymph nodes, revealed no residual malignancy, showing a pathological complete response (pCR). The achievement of pCR in this case illustrates the effectiveness of neoadjuvant chemotherapy and suggests that S-1/CDDP may be a useful preoperative option for advanced duodenal cancer with lymph node metastasis.